2014
DOI: 10.7860/jcdr/2014/8571.4589
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Doppler: A Tool for Non-Invasive Prediction of Esophageal Varices in Cirrhosis

Abstract: Background and Objectives: Esophageal varices (EV), a major complication of liver cirrhosis, can lead to life threatening gastrointestinal (GI) bleeding. Esophagogastroduodenoscopy (EGD) is the gold standard for diagnosis and management of esophageal varices. However, it is not always available in resourceconstrained settings.This study was aimed at evaluating portal vein indices (PVI) using Doppler on ultrasound abdomen, which is more widely available, as tools to predict the presence of EV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This parameter represents the ratio between the cross-sectional area (cm 2 ) and the blood flow velocity (cm/sec) of the PV: CIx = (pP2/4)/PV mean, where P is the PV diameter and PV mean represents the mean portal flow velocity [ 83 ]. Although the first results were promising for the detection of varices, large varices [ 84 ] and red spots [ 85 ], other studies failed to confirm these results [ 86 ] or demonstrated better predictive values for other indices, such as PV velocity [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…This parameter represents the ratio between the cross-sectional area (cm 2 ) and the blood flow velocity (cm/sec) of the PV: CIx = (pP2/4)/PV mean, where P is the PV diameter and PV mean represents the mean portal flow velocity [ 83 ]. Although the first results were promising for the detection of varices, large varices [ 84 ] and red spots [ 85 ], other studies failed to confirm these results [ 86 ] or demonstrated better predictive values for other indices, such as PV velocity [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…A sample size of 64 was calculated using the sensitivity formula with a confidence level of 90%, a level of significance of 10%, the sensitivity of the test being 96% 7 and a reasonable estimate of key proportions to be measured in the study was 16% 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Portal vein velocity (PVV) has high sensitivity and a positive predictive value (PPV) for esophageal varices formation in cirrhosis. PVV with a rule-out cutoff value greater than 19 cm/s has 96% sensitivity for screening of esophageal varices 7 .…”
Section: Introductionmentioning
confidence: 99%
“…One parameter associated with EV is the PV velocity [16][17][18]. Unfortunately, the association seemed not strong enough and even showed insignificant in some studies, especially on SEV [18][19][20].…”
Section: Introductionmentioning
confidence: 99%